Microbiological Characteristics of Gouda Cheese Manufactured with Pasteurized and Raw Milk during Ripening Using Next Generation Sequencing - Park, Wonseo; Yoo, Jayeon; Oh, Sangnam; Ham, Jun-sang; Jeong, Seok-geun; Kim, Younghoon (Food science of animal resources, 2019)
Gouda cheese, one of most popular cheeses in the Korea, has been produced from only pasteurized milk in Korean dairy farms. Recently, it has become legally possible to produce ripened cheese manufactured with raw milk in Korea. In the present study, we investigated the physico-chemical and microbiological characteristics of Gouda cheese manufactured with raw (R-GC) or pasteurized milk (P-GC) during manufacturing and ripening. Particularly, this study characterized the bacterial community structure of two cheese types, which are produced without pasteurization during ripening based on next generation sequencing of 16S rRNA gene amplicons. During ripening, protein and fat content increased slightly, whereas moisture content decreased in both P-GC and R-GC. At the 6 wk of ripening, R-GC became softer and smoother and hence, the values of hardness and gumminess, chewiness in R-GC was lower than that of P-GC. Metagenomic analysis revealed that the bacterial genera used a starter cultures, namely and were predominant in both P-GC and R-GC. Moreover, in R-GC, the proportion of coliform bacteria such as , , , and were detected initially but not during ripening. Taken together, our finding indicates the potential of manufacturing with Gouda cheese from raw milk and the benefits of next generation sequencing for microbial community composition during cheese ripening.